Cultural Dynamics in a Globalized World Proceedings of the Asia- Pacific research in Social Sciences and Humanities, Depok, Indonesia, November 7-9, 2016, Topics in arts and humanities - Budiman, Manneke; Budianta, Melani; Kusno, Abidin; Moriyama, Mikihiro (Taylor & Francis, 2018)
The book contains essays on current issues in arts and humanities in which peoples and cultures compete as well as collaborate in globalizing the world while maintaining their uniqueness as viewed from cross- and inter-disciplinary perspectives. The book covers areas such as literature, cultural studies, archaeology, philosophy, history, language studies, information and literacy studies, and area studies. Asia and the Pacific are the particular regions that the conference focuses on as they have become new centers of knowledge production in arts and humanities and, in the future, seem to be able to grow significantly as a major contributor of culture, science and arts to the globalized world. The book will help shed light on what arts and humanities scholars in Asia and the Pacific have done in terms of research and knowledge development, as well as the new frontiers of research that have been explored and opening up, which can connect the two regions with the rest of the globe.